Literarisches System in Österreich 1933/1938-1945: Zensur und Förderung - Literarische Vereine - Anthologien - Baur, Uwe (2021)
The literature of the National Socialist period is mostly considered person-centric, as prehistory or post-history of epochs deemed significant, rather than as an independent, intentionally closed system within the framework of a media dictatorship.